2009
DOI: 10.2131/jts.34.693
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo evaluation of mutagenicity of fucoxanthin (FX) and its metabolite fucoxanthinol (FXOH)

Abstract: fucoxanthin (FX), was evaluated by in vitro Ames test, and of FX by in vivo micronucleus test. In in vitro Ames test, bacterial reverse mutation was examined by using Salmonella typhimurium strains TA98, TA100, TA1535 and TA1537, and Escherichia coli WP2uvr -vation by S9 mix in the preincubation method, and mutagenicity of FXOH was found to be negative in all cases. In in vivo micronucleus test, mice were orally administered with FX at doses of 500, 1,000 and 2,000 mg/kg, and the bone marrow cells were taken 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 17 publications
1
35
0
Order By: Relevance
“…Beppu and colleagues, observed the incidence of micronucleus and mutagenicity of fucoxanthin in bone marrow cells of mice that were orally administered for 24h. The results for micronucleus and mutagenicity were found to be negative (Beppu et al, 2009). …”
Section: Fucoxanthinmentioning
confidence: 99%
“…Beppu and colleagues, observed the incidence of micronucleus and mutagenicity of fucoxanthin in bone marrow cells of mice that were orally administered for 24h. The results for micronucleus and mutagenicity were found to be negative (Beppu et al, 2009). …”
Section: Fucoxanthinmentioning
confidence: 99%
“…Subsequently, Beppu et al . [56] indicated that fucoxanthin had no genotoxic/mutagenic effect on the bone marrow cells of mice. Iio et al .…”
Section: Bioavailability Metabolism and Safety Of Fucoxanthinmentioning
confidence: 99%
“…In the 13-week oral dose study, the no-observed-adverse-effect level of fucoxanthin was 200 mg/kg body weight under the tested subchronic dose condition. These studies suggested that fucoxanthin was a safe compound and did not exhibit toxicity and mutagenicity under these experimental conditions [3,34,56]. …”
Section: Bioavailability Metabolism and Safety Of Fucoxanthinmentioning
confidence: 99%
“…Fucoxanthin toxicity has arisen as a concern from results of mice experiments 37,38 . Fucoxanthin was orally administered at doses of 500 and 1,000 mg/kg to male and female ICR mice for 30 days.…”
Section: Fucoxanthin Absorption and Safetymentioning
confidence: 99%